2020
DOI: 10.1055/s-0040-1708559
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Experience with Neurally Adjusted Ventilatory Assist in Infants with Severe Bronchopulmonary Dysplasia

Abstract: Objective The aim of this study is to determine patterns of neurally adjusted ventilatory assist (NAVA) use in ventilator-dependent preterm infants with evolving or established severe bronchopulmonary dysplasia (sBPD) among centers of the BPD Collaborative, including indications for its initiation, discontinuation, and outcomes. Study Design Retrospective review of infants with developing or established sBPD who were placed on NAVA after ≥4 weeks of mechanical ventilation and were ≥ 30 weeks of postm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Despite consensus recommendations from collaborating centers, significant variations in care have been documented ( 21 ). In a recent publication from the Children's Hospital Neonatal Consortium (CHNC), researchers found significant differences in ventilator modes and practices; 51% were treated with volume-control or volume guarantee, 43% with pressure-control, and 6% with neurally adjusted ventilatory assist (NAVA) ( 28 ). The use of non-invasive modes was equally variable; 41% were treated with high-flow nasal cannula (HFNC), 28% with low-flow nasal cannula (LFNC), 26% with continuous positive airway pressure (CPAP), and 5% with other modes ( 28 ).…”
Section: An Alternative Respiratory Support Strategy For Infants With...mentioning
confidence: 99%
“…Despite consensus recommendations from collaborating centers, significant variations in care have been documented ( 21 ). In a recent publication from the Children's Hospital Neonatal Consortium (CHNC), researchers found significant differences in ventilator modes and practices; 51% were treated with volume-control or volume guarantee, 43% with pressure-control, and 6% with neurally adjusted ventilatory assist (NAVA) ( 28 ). The use of non-invasive modes was equally variable; 41% were treated with high-flow nasal cannula (HFNC), 28% with low-flow nasal cannula (LFNC), 26% with continuous positive airway pressure (CPAP), and 5% with other modes ( 28 ).…”
Section: An Alternative Respiratory Support Strategy For Infants With...mentioning
confidence: 99%
“…In multiple small prospective cross‐over studies in infants with RDS or evolving BPD, NAVA has been shown to reduce the PIP, the fraction of inspired oxygen, and the work of breathing compared with other patient‐triggered ventilatory modes 28,46–55 (Table 4). In a multi‐center review of current clinical practice, NAVA was successful as a weaning mode of ventilation in infants with severe BPD 67% of the time 56 …”
Section: Neurally Adjusted Ventilatory Assistmentioning
confidence: 99%
“…In every waveform pattern, these median proportions were used as thresholds for dividing data units into the H-and L-groups. (e.g., in one unit, if the phasic pattern was 62%, the central apnea pattern was 13%, the irregular low-voltage pattern was 12%, and the tonic (15,16) 15 (14,16) .001…”
Section: Edi Waveform Patterns and Ventilatory Parametersmentioning
confidence: 99%
“…These infants develop an unstable respiratory condition or need to have their ventilatory mode changed from NAVA. [16][17][18] However, there are limited clinical indicators of whether infants can be appropriately ventilated by NAVA.…”
Section: Introductionmentioning
confidence: 99%